Acoustic emission method for determining time of fatigue crack initiation of metal under hydrogen environment

By acquiring acoustic emission signals in real time and observing in-situ bubbles, the initiation time of metal fatigue cracks in a hydrogen environment can be identified, solving the problem of accurate determination in existing technologies and achieving efficient and accurate determination of crack initiation time.

CN123045830APending Publication Date: 2026-11-06ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611297956.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing technologies are insufficient to accurately determine the initiation time of metal fatigue cracks in a hydrogen environment. Traditional methods are prone to misjudgment, and the equipment is expensive and the operation is complex, making them unsuitable for widespread application in routine fatigue testing.

Method used

By acquiring acoustic emission signals of metal samples in a hydrogen environment in real time, identifying the slope changes of cumulative count and cumulative energy curves, and combining this with in-situ bubble observation, the fatigue crack initiation time can be determined.

Benefits of technology

It enables in-situ, real-time, and accurate determination of crack initiation time in a hydrogen environment, improving the accuracy and reliability of the determination. It has low equipment requirements, is easy to operate, and is convenient for promotion and application in conventional laboratories and industrial sites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123045830A_ABST
    Figure CN123045830A_ABST
Patent Text Reader

Abstract

This invention relates to hydrogen energy safety non-destructive testing technology, aiming to provide an acoustic emission method for determining the initiation time of fatigue cracks in metals under hydrogen conditions. The method includes: applying a cyclic load to a metal sample in a hydrogen environment and acquiring acoustic emission signals in real time to obtain a curve showing the cumulative amount of acoustic emission characteristic parameters changing over time; identifying the slope change characteristics of the curve, and determining the moment when the curve transitions from a stable linear growth segment to a point where the slope is lower than that segment as the fatigue crack initiation time. This invention is the first to discover and utilize the phenomenon that the slope of the curve showing the cumulative count and / or cumulative energy changing over time suddenly drops from a stable high value and remains so, as a macroscopic indicator of the crack initiation time; it allows for in-situ real-time acquisition of the initiation time without interrupting the experiment or offline analysis; and it can also introduce in-situ bubble observation as physical verification, achieving dual verification between acoustic methods and physical phenomena, improving the accuracy and reliability of the determination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hydrogen energy safety detection and non-destructive testing technology, specifically relating to a method for determining the fatigue crack initiation time of metallic materials in real time by using acoustic emission cumulative counting and / or changes in the slope of the cumulative energy curve in a hydrogen environment. Background Technology

[0002] Hydrogen energy, as a clean and efficient secondary energy source, plays a vital role in the global transition to a low-carbon economy. Type I all-metal hydrogen storage pressure vessels remain widely used in commercial hydrogen storage due to their structural integrity and lower manufacturing costs. However, hydrogen embrittlement reduces the ductility and fatigue life of the metal, posing a significant risk to the safe operation of the vessel.

[0003] Accurately assessing the impact of hydrogen on fatigue life hinges on precisely capturing the crack initiation moment. Traditional fatigue testing relies on monitoring stress-strain or displacement-time curves, but the determined crack initiation time ranges are very broad, lacking practical guidance. Liquid penetrant and surface replication methods require frequent interruptions to apply penetrants or prepare replicas, disrupting test continuity and the in-situ environment. While in-situ scanning electron microscopy and synchrotron X-ray computed tomography can track cracks in situ, the equipment is expensive and the operation complex, making widespread application in routine fatigue testing difficult. Digital image correlation methods cannot be effectively used in gaseous or electrochemically hydrogen-filled environments due to environmental limitations.

[0004] Acoustic emission (AE) technology can detect transient elastic waves generated in real time by rapid energy release from microcrack propagation and dislocation motion within materials, offering high temporal resolution and non-destructive characteristics. However, existing AE fatigue detection research largely focuses on the crack propagation stage. Whether using cumulative counting or cumulative energy parameters, a ingrained technical understanding has emerged, characterized by an "increasing slope of the cumulative curve." Guided by this inertia, those skilled in the art often tend to look for abnormally high slopes in the curve when attempting to determine crack initiation using AE. For the initiation stage before macroscopic cracks appear, especially under complex environmental interference such as liquid-phase hydrogen charging, this ingrained technical understanding stemming from the crack propagation stage constitutes a technical obstacle to identifying the true acoustic emission characteristics of crack initiation. This leads to an inability to effectively extract accurate criteria for the initiation moment and may even result in misjudgment due to differences in signal characteristics.

[0005] Therefore, there is an urgent need for a method that can determine the initiation time of metal fatigue cracks in a hydrogen environment in situ, in real time, and accurately, in order to meet the needs of safety assessment of hydrogen energy equipment. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide an acoustic emission method for determining the initiation time of metal fatigue cracks in a hydrogen environment.

[0007] To solve the technical problem, the solution of the present invention is:

[0008] An acoustic emission method for determining the initiation time of fatigue cracks in metals under hydrogen conditions is provided, comprising the following steps:

[0009] S1. Apply cyclic loading to the metal sample to be tested in a hydrogen environment and collect acoustic emission signals in real time to obtain the curve of the cumulative amount of acoustic emission characteristic parameters changing with time.

[0010] S2. Identify the slope change characteristics of the curve, and determine the moment when the curve changes from a stable linear growth segment to a point where the slope is lower than that of the stable linear growth segment as the fatigue crack initiation time.

[0011] As a preferred embodiment of the present invention, the cumulative amount of the acoustic emission characteristic parameters refers to the cumulative acoustic emission count and / or the cumulative acoustic emission energy.

[0012] As a preferred embodiment of the present invention, the method for confirming the turning point is as follows: monitoring the slope change of the curve, and determining the moment when the slope begins to decrease as the fatigue crack initiation time when the following two conditions are met simultaneously:

[0013] (1) The slope decreases for more than the preset duration;

[0014] (2) The slope decreases by more than the preset ratio.

[0015] As a preferred embodiment of the present invention, it further includes a verification step: using a camera device to record in situ the evolution of bubbles generated on the sample surface due to electrochemical hydrogen charging; taking the moment when the observed bubbles begin to propagate directionally in a direction approximately perpendicular to the fatigue load direction as physical evidence of crack initiation, and cross-verifying it with the determined fatigue crack initiation time.

[0016] As a preferred embodiment of the present invention, the hydrogen environment is achieved by in-situ hydrogen charging or pre-charging; the in-situ hydrogen charging or pre-charging is independently achieved by electrochemical hydrogen charging or gas-phase hydrogen charging.

[0017] As a preferred embodiment of the present invention, the metal sample to be tested is a high-strength steel, low-alloy steel or aluminum alloy with a yield strength of not less than 250 MPa, suitable for high-pressure hydrogen environments.

[0018] As a preferred embodiment of the present invention, a stress control mode is adopted when applying cyclic load, and the stress ratio is 0.1.

[0019] This invention also provides an acoustic emission determination system for the initiation time of fatigue cracks in metals under hydrogen conditions, comprising:

[0020] The synchronous control module controls the hydrogen charging device to place the metal sample under test in a hydrogen environment while applying a cyclic load to the metal sample under test.

[0021] An acoustic emission acquisition module, connected to the synchronization control module, acquires acoustic emission signals in real time and generates a curve showing the cumulative amount of acoustic emission characteristic parameters changing over time. The acoustic emission characteristic parameters include cumulative count and / or cumulative energy.

[0022] The feature recognition module is used to perform real-time piecewise linear fitting on the curve and continuously calculate the slope of the current stable linear segment. If it is detected that the slope of the curve decreases from the current stable value, and the decrease exceeds a preset ratio and the decrease continues for more than a preset duration, the moment when the slope begins to decrease is marked as the fatigue crack initiation time and output.

[0023] The present invention further provides an electronic device, including a memory and a processor, wherein the memory stores a computer program, and the processor executes the program to implement the method described above.

[0024] The present invention further provides a computer-readable storage medium storing a computer program that, when executed by a processor, implements the method described above.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] 1. This invention breaks through the conventional approach of relying mainly on "increasing slope" to characterize crack propagation in existing acoustic emission detection. It is the first to discover and utilize the phenomenon that the slope of the curve showing the cumulative acoustic emission count and / or cumulative energy changes over time suddenly drops from a stable high value and remains so, as a macroscopic indicator of crack initiation. This counterintuitive pattern reveals the inherent characteristic of abrupt changes in the acoustic emission event rate at the moment of microcrack initiation. This invention allows for in-situ, real-time acquisition of initiation time without interrupting experiments or offline analysis.

[0027] 2. This invention introduces in-situ bubble observation as a physical verification method. It utilizes the intuitive visual feature of hydrogen bubbles expanding along the direction perpendicular to the load to provide reliable evidence of crack initiation for acoustic emission determination. This achieves dual verification between acoustic methods and physical phenomena, improving the accuracy and reliability of the determination.

[0028] 3. Compared with existing displacement methods, permeation methods, surface replication methods and expensive microscopic observation techniques, the method of this invention has low equipment requirements, is simple to operate, is not limited by hydrogen-filled environments, and is easy to promote and apply in conventional laboratories and even industrial sites.

[0029] 4. This method provides an accurate and convenient means of capturing the crack initiation moment for hydrogen embrittlement research and full life assessment of hydrogen storage containers, which helps to reveal the early behavior of hydrogen-induced cracks and establish a more accurate life prediction model.

[0030] 5. Compared with in-situ bubble observation that relies on vision, the acoustic emission determination method of the present invention is not affected by environmental factors such as bubble accumulation, obstruction or lighting conditions, and has stronger environmental adaptability and higher determination robustness. It can still stably capture the moment of crack initiation even when bubble observation fails. Attached Figure Description

[0031] Figure 1 The cumulative acoustic emission count-time curve and piecewise linear fitting graph of sample 1 are shown.

[0032] Figure 2 The cumulative acoustic emission count-time curve and piecewise linear fitting graph for sample 2 are shown.

[0033] Figure 3 The cumulative acoustic emission energy-time curve and piecewise linear fitting graph of sample 1 are shown.

[0034] Figure 4 The cumulative acoustic emission energy-time curve and piecewise linear fitting diagram for sample 2 are shown.

[0035] Figure 5 Images of the crack initiation and propagation process in sample 1, recorded from in-situ bubble observation. Detailed Implementation

[0036] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited thereto.

[0037] It should be noted that although this invention uses in-situ liquid-phase electrochemical hydrogen charging as a specific embodiment, those skilled in the art will understand that acoustic emission technology detects transient elastic waves generated within the material due to damage. Its signal characteristics mainly depend on the internal mechanical response and damage mode transition of the material, and are independent of the specific medium providing the hydrogen environment. Therefore, as long as the sample is in a hydrogen environment, hydrogen-induced crack initiation under cyclic loading will trigger the aforementioned abrupt change in the acoustic emission event rate. The method of this invention is also applicable to the determination of fatigue crack initiation under other hydrogen environments, such as electrochemical pre-charging, in-situ gas-phase hydrogen charging, and gas-phase pre-charging; only the test parameters need to be adjusted according to the specific environment.

[0038] I. Implementation Scheme of the Invention

[0039] The acoustic emission determination method for the initiation time of fatigue cracks in metals under hydrogen conditions provided by this invention includes the following steps:

[0040] S1. During the process of applying cyclic loading to the metal sample to be tested and placing it in a hydrogen environment, the acoustic emission signal is collected in real time to obtain the cumulative count and / or the curve of cumulative energy changing with time.

[0041] During testing, the metal sample to be tested is placed in a hydrogen environment. Specifically, while applying a cyclic load, the gauge section of the sample is in-situ charged with hydrogen using an electrochemical hydrogen charging device. The hydrogen environment can be achieved through in-situ hydrogen charging or pre-charging; the in-situ hydrogen charging or pre-charging is achieved independently using either electrochemical hydrogen charging or gas-phase hydrogen charging. For example, an electrochemical hydrogen charging device can be constructed using a three-electrode system with the sample as the working cathode, a platinum sheet as the counter electrode, and NaOH solution as the electrolyte to provide the required hydrogen environment for testing. The cyclic load is in stress-controlled mode with a stress ratio of 0.1. An example of the metal sample material is high-strength steel with a yield strength greater than 520 MPa (e.g., 4130X steel for hydrogen storage containers).

[0042] This method is also applicable to other metallic materials that will undergo hydrogen embrittlement in a hydrogen environment, such as low-alloy steel or aluminum alloys with a yield strength of not less than 250 MPa; the test parameters can be adjusted according to the material properties during the test.

[0043] S2. Perform piecewise linear fitting on the cumulative count-time curve and / or cumulative energy-time curve to identify the slope change characteristics of the curve; determine the moment when the curve changes from a stable linear growth segment to a point where the slope is lower than that stable linear growth segment as the fatigue crack initiation time.

[0044] In the initial loading stage, the curve exhibits a low initial slope; subsequently, the slope gradually increases and maintains a stable linear growth for a certain period of time after each increase; however, after a certain moment, the slope of the curve suddenly decreases and remains at this decreased slope for a considerable period of time; the turning point when the slope begins to decrease from a stable value is determined as the fatigue crack initiation time.

[0045] The criteria for determining the turning point are: if the slope of the cumulative count-time curve and / or the cumulative energy-time curve drops by more than a preset proportion after the stable linear growth phase, and the duration of the slope after the drop exceeds a preset minimum duration, then the point at which the slope begins to drop is defined as the crack initiation time.

[0046] As an example, the preset ratio is set to be more than 10% of the stable slope, and the preset minimum duration is not less than 1000 seconds. It should be noted that the preset ratio and the preset minimum duration are not fixed. Those skilled in the art can determine the threshold suitable for a specific working condition through a limited number of experiments based on the specific material properties, hydrogen charging conditions, and load parameters.

[0047] S3: As an optional verification step, during the test, a camera device is used to record in situ the evolution of bubbles generated on the sample surface due to electrochemical hydrogen charging; the moment when the observed bubbles begin to expand in a direction approximately perpendicular to the fatigue load direction is used as the physical criterion for crack initiation, and cross-verified with the initiation time determined in S2; if the time deviation between the two is within the preset threshold range, the acoustic emission determination result is confirmed to be valid.

[0048] II. Specific Application Examples

[0049] The material used in this embodiment was an actual seamless hydrogen storage pressure vessel with a diameter of 559×31.6mm, grade 4130X. The entire vessel underwent double-sided quenching and tempering heat treatment. The average mechanical properties of the material are: yield strength 717MPa, tensile strength 826.5MPa. The specimen used was a plate fatigue specimen. Before the test, the gauge length of the specimen was manually polished sequentially using 180-grit, 320-grit, 600-grit, and 1000-grit sandpaper to obtain a smooth and repeatable surface condition.

[0050] The experimental setup consisted of an MTS servo-hydraulic testing system, an electrochemical hydrogen charging three-electrode system, an acoustic emission acquisition system, and a high-definition camera. Tensile low-cycle fatigue tests were conducted on the MTS servo-hydraulic testing system using a stress-controlled mode, with the peak stress being the yield strength and a stress ratio R=0.1. Electrochemical hydrogen charging employed a three-electrode system with a 1 mol / L NaOH solution as the electrolyte and a charging current density of 0.08 mA / cm². A platinum sheet was used as the counter electrode, and the sample as the working cathode. Hydrogen charging and mechanical loading started synchronously. The acoustic emission sensor was mounted as close as possible to the gauge length using a clamp. Acquisition parameters were set as follows: pre-trigger time 256 μs, peak definition time 300 μs, impact definition time 600 μs, and impact lock-up time 1000 μs. The sensor sensitivity and reliability were verified through a lead-breaking test before the formal test. Simultaneously, the high-definition camera was positioned directly above the sample surface, continuously recording at 30 FPS and 4 Mbps bitrate. The camera was fixed below the actuator to maintain relative stillness with the sample and prevent field-of-view jitter.

[0051] Two parallel tests were conducted under the above conditions, with the samples numbered 1 and 2. Figure 1 , Figure 2 The acoustic emission cumulative count-time curves for the two samples are given respectively. Piecewise linear fitting lines are superimposed on the figures, and the slope S and goodness of fit R² for each segment are labeled.

[0052] from Figure 1 and Figure 2 As can be seen from the graphs, the curves in both figures exhibit a highly consistent slope variation pattern: after the experiment begins, the slope of the cumulative count curve is relatively low; subsequently, the slope gradually increases, and after each increase, it maintains a stable linear growth for a certain period of time; however, after reaching a certain characteristic moment (such as...), the slope changes... Figure 1 15832 seconds and Figure 2 At 6533 s, the slope of the curve decreased significantly and remained at this lower slope for a considerable period of time; taking sample 1 as an example, at 15832 s, the slope of the cumulative count curve decreased from 18.2 × 10⁻⁶ in the stable phase. 5 The count / second decreased to 16.3 × 10 5 The count / second decreased by 10.4%, and this low-slope phase lasted for approximately 4000 s. Taking sample 2 as an example, the slope of sample 2 decreased from 11 × 10 at 6533 s. 5 The count / second decreased to 9×10 5 The count is per second, lasting approximately 3000 seconds. In the final stage, approximately 2000 seconds before fracture, the curve accelerates due to intense acoustic emission activity until fracture. According to the criteria of the present invention, the moment when the slope begins to decrease from its stable value is determined as the crack initiation time for each specimen.

[0053] Figure 3 and Figure 4 The cumulative acoustic emission energy-time curves and piecewise linear fitting results for the two samples are presented respectively. As can be seen from the figures, the cumulative energy curve exhibits a pattern highly consistent with the cumulative counting curve: near the same inflection point (considering the existence of measurement error), the curve slope suddenly decreases from a stable high value and remains so. Taking sample 1 as an example, the slope of the cumulative energy curve decreases from 2.0 × 10⁻⁶ in the stable segment... 4 Decreased to 1.7 × 10 4 (Unit: EU / s), the decrease was approximately 15%, with a turning point of 15751 s, which is within a reasonable range from the germination time of 15832 s determined by the cumulative count curve. The above results verify that the determination method of the present invention is applicable to different acoustic emission characteristic parameters.

[0054] Figure 5 Taking sample 1 as an example, typical images of bubble evolution recorded by in-situ photography are presented. Before the initiation moment determined by acoustic emission, only dispersed tiny hydrogen bubbles are visible on the sample surface; Figure 5 At the initiation moment shown in (a), the second bubble begins to appear, arranged approximately perpendicular to the loading axis. From Figure 5 (b) and Figure 5 In figure (c), several bubbles can be observed to be closely arranged and perpendicular to the loading axis, as indicated by the black line segment. This is because the newly formed surface of the crack in the sample provides nucleation sites for the bubbles. This visually demonstrates that the crack... Figure 5 The bubble germinated and began to expand at time 15329s, as shown in (a). The earliest frame time when the bubble began to show directional expansion characteristics was compared with the acoustic emission determination germination time. The time difference between the two was 503 seconds, which is within 5% of the total test duration, thus forming a good mutual verification. Figure 5(d) is an image of the crack penetrating the surface of the specimen. The comparison shows that the crack path depicted by the bubble observation method is highly consistent with the physically measured crack trajectory. This not only verifies the reliability of the observation method but also demonstrates that in the early stages of crack initiation (the stage invisible to the naked eye), the bubble signal can become a sensitive indicator of the crack initiation time before the macroscopic morphology.

[0055] For sample 2, due to the large amount of bubbles accumulating and obstructing the field of view during the crack initiation period, in-situ imaging could not capture the exact moment of crack initiation, and could only lock the initiation time within a wide range of 5400 to 7000 s. However, the acoustic emission cumulative count curve showed a steep drop in slope at 6533 s, similar to that of sample 1, verifying the repeatability of this acoustic emission characteristic signal. According to the determination criteria of the present invention, this moment was determined as the crack initiation time. The comparison results of sample 2 show that when visual observation fails due to environmental factors such as obstruction and can only provide a wide time range, the acoustic emission determination method of the present invention can still stably provide an accurate initiation time point, demonstrating higher temporal resolution and engineering practical robustness. Table 1 summarizes the initiation time determination results and lifetime data of the two sets of samples.

[0056] Table 1. Comparison of Acoustic emission determination of germination time and in-situ bubble observation results.

[0057]

[0058] As shown in Table 1, for sample 1, the germination times for acoustic emission cumulative counting and cumulative energy determination are 15832 s and 15751 s, respectively, with a difference of only 81 s. Both are within 5% of the bubble observation results, demonstrating a high degree of agreement between the three independent methods. For sample 2, the germination times for cumulative counting and cumulative energy determination are 6533 s and 6517 s, respectively, with a deviation of only 16 s. Even when bubble observation can only provide an interval due to obstruction, the acoustic emission method still provides accurate and consistent germination time points. These results indicate that the acoustic emission determination method of this invention has high self-consistency across different characteristic parameters and is mutually corroborated by physical verification methods.

[0059] Based on the above experimental results and combined with existing research theories, the applicant believes that the physical mechanism underlying the above experimental phenomena is as follows: In the stable stage of cyclic loading, the material interior is dominated by dispersed dislocation motion and local plastic deformation. These microscopic processes continuously generate a large number of acoustic emission events, manifested as a stable linear increase (high slope) in the cumulative count curve. When a microcrack truly initiates, the damage mode shifts from "dispersed damage" to "local crack formation and propagation," and the energy release form undergoes a fundamental change, leading to a phased decrease in the acoustic emission event rate. Therefore, macroscopically, this manifests as a sudden decrease in the slope of the cumulative count curve. The above analysis is phenomenologically confirmed in in-situ bubble observations: the starting moment of directional bubble propagation closely matches the turning point of the acoustic emission slope, which also explains why traditional methods based on "slope increase" cannot effectively capture the initiation moment.

[0060] The specific embodiments of the present invention have been described above. It should be understood that the present invention is not limited to the specific embodiments described above, and those skilled in the art can make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. An acoustic emission method for determining the initiation time of fatigue cracks in metals under hydrogen conditions, characterized in that, Includes the following steps: S1. Apply cyclic loading to the metal sample to be tested in a hydrogen environment and collect acoustic emission signals in real time to obtain the curve of the cumulative amount of acoustic emission characteristic parameters changing with time. S2. Identify the slope change characteristics of the curve, and determine the moment when the curve changes from a stable linear growth segment to a point where the slope is lower than that of the stable linear growth segment as the fatigue crack initiation time.

2. The method according to claim 1, characterized in that, The cumulative amount of the acoustic emission characteristic parameters refers to the cumulative acoustic emission count and / or the cumulative acoustic emission energy.

3. The method according to claim 1, characterized in that, The method for confirming the turning point is as follows: monitor the slope change of the curve, and determine the moment when the slope begins to decrease as the fatigue crack initiation time when the following two conditions are met simultaneously: (1) The slope decreases for more than the preset duration; (2) The slope decreases by more than the preset ratio.

4. The method according to claim 1, characterized in that, Further verification steps are also included: using a camera device to record in situ the evolution of bubbles generated on the sample surface due to electrochemical hydrogen charging; the moment when the observed bubbles begin to propagate directionally in a direction roughly perpendicular to the fatigue load direction is used as physical evidence of crack initiation, and cross-verified with the determined fatigue crack initiation time.

5. The method according to claim 1, characterized in that, The hydrogen environment is achieved through in-situ hydrogen charging or pre-charging; the in-situ hydrogen charging or pre-charging is achieved independently by electrochemical hydrogen charging or gas-phase hydrogen charging.

6. The method according to claim 1, characterized in that, The metal sample to be tested is a high-strength steel, low-alloy steel or aluminum alloy with a yield strength of not less than 250 MPa, used in high-pressure hydrogen environments.

7. The method according to claim 1, characterized in that, When applying cyclic loads, a stress control mode is used with a stress ratio of 0.

1.

8. An acoustic emission determination system for the initiation time of fatigue cracks in metals under hydrogen conditions, characterized in that, include: The synchronous control module controls the hydrogen charging device to place the metal sample under test in a hydrogen environment while applying a cyclic load to the metal sample under test. An acoustic emission acquisition module, connected to the synchronization control module, acquires acoustic emission signals in real time and generates a curve showing the cumulative amount of acoustic emission characteristic parameters changing over time. The acoustic emission characteristic parameters include cumulative count and / or cumulative energy. The feature recognition module is used to perform real-time piecewise linear fitting on the curve and continuously calculate the slope of the current stable linear segment. If it is detected that the slope of the curve decreases from the current stable value, and the decrease exceeds a preset ratio and the decrease continues for more than a preset duration, the moment when the slope begins to decrease is marked as the fatigue crack initiation time and output.

9. An electronic device, characterized in that, The method includes a memory and a processor, wherein the memory stores a computer program, and the processor executes the program to implement the method as described in any one of claims 1 to 7.

10. A computer-readable storage medium, characterized in that, The computer-readable storage medium stores a computer program that, when executed by a processor, implements the method as described in any one of claims 1 to 7.